Computational Thinking Assessment: Bibliometric Analysis-VOSviewer - Ria, Reny Refitaningsih Peby (Universitas Nusantara PGRI Kediri, 2024)
Computational thinking is a very important ability in the transitional era of the industrial revolution 4.0 to 5.0 because it has a role in supporting problem solving, especially in the field of Education by applying computer thinking. Seeing the role of computational thinking in education, an assessment is needed to assess students' ability to apply computational thinking to solve problems, especially in learning computer science. Therefore, the aim of this study is to present a high-quality bibliometric review of various literature on assessment computational thinking. This type of research is bibliometric analysis using VOSviewer. Literature was collected from the Scopus database of 191 articles published in 2019-2023. The results of this study show that in the network visualization results there are 5 clusters, namely cluster 1 (43 items), cluster 2 (31 items), cluster 3 (27 items), cluster 4 (21 items), and cluster 5 (19 items). Meanwhile, on the results of overlay visualization and density visualization, it can be seen that the computational thinking assessment research shows that when it is associated with the themes of instrument, validity, reliability, and computer science education, not much research has been done so that there are opportunities for renewable research by taking these themes.